2006
DOI: 10.1111/j.1365-2044.2006.04550.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein cross‐contamination during batch cleaning and autoclaving of the ProSeal laryngeal mask airway

Abstract: We tested the hypothesis that protein cross-contamination occurs during batch cleaning and autoclaving of a reusable extraglottic airway device, the ProSeal TM laryngeal mask airway. At the end of each day for 10 days, nine laryngeal mask airways that had been used for non-intra-oral surgery were cleaned and autoclaved alongside a new unused laryngeal mask airway. In addition, a new unused laryngeal mask airway underwent the same cleaning and autoclaving procedures in isolation. Protein staining was more frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Protein contamination of reused medical devices can cause the transmission of prion proteins, with PLMA reuse running the risk of aiding in the transmission of variant Creutzfelt-Jacob disease. Also, when many PLMAs are washed together, protein cross-contamination can occur [28]. For such reasons, using disposable devices which have no difference in effectiveness lowers the risk of contamination and is more hygienic.…”
Section: Discussionmentioning
confidence: 99%
“…Protein contamination of reused medical devices can cause the transmission of prion proteins, with PLMA reuse running the risk of aiding in the transmission of variant Creutzfelt-Jacob disease. Also, when many PLMAs are washed together, protein cross-contamination can occur [28]. For such reasons, using disposable devices which have no difference in effectiveness lowers the risk of contamination and is more hygienic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that routine cleaning and autoclaving do not remove protein material from reusable laryngeal mask airway devices (LMADs). [7][8][9][10] Compared with the PLMA, the SLMA's design has several refinements. First, it is a single-use latex-free device; each SLMA is prepared in a separate sterile package.…”
Section: Résumémentioning
confidence: 99%
“…This advice is based on evidence that microscopic traces of tissue can remain on surgical instruments after washing, autoclaving, and disinfection and that routine methods for cleaning SADs do not completely remove protein deposits . Protein cross‐contamination occurs during batch cleaning and autoclaving and furthermore, sterilisation methods do not denature prions .…”
Section: Disposability and Variant Creutzfeldt‐jakob Diseasementioning
confidence: 99%